PERSEPSI MASYARAKAT TERHADAP PENGUNAAN TRANSPORTASI ONLINE ( GRAB ) DI KOTA BIMA - Agustina Agustina; Intisari Haryanti (JURNAL MANAJEMEN, 2021)
AbstractThis study aims to determine: public perception of the use of online transportation (GRAB) in the city of Bima. This research is a descriptive type of research. The population of this study is that which is used in this study, namely objects/subjects that have certain qualities and characteristics set by the researchers to be studied and then drawn conclusions. The data analysis technique used is the validity test, reliability test, t-Test One sample test.The results show that: the results of the calculations in the one sample test table above can be seen that the value of t (hgicount) is 52,719. The value of df (degree of freedom) or degrees of freedom is 0.000. Thus the alternative hypothesis (Ha) which reads that the community has a good perception of the existence of online transportation (GRAB) in the Bima city area is "accepted"